Studi Eksperimen Penggunaan Diesel Particulat Filter Terhadap Temperatur Oli Mesin, Air Radiator, Dan Exhaust Manifold Mesin Diesel - Kurniawan, Moch. Aziz; Wibowo, Helmi; Eska Fahmadi , Aat; Amin, Nasrul; Farras, Muhammad (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2025)
The use of vehicles using diesel engines is increasing and has a direct impact on increasing exhaust emissions, especially particulate matter (PM), which is harmful to health and the environment. This study aims to analyze the installation of a honeycomb Diesel Particulate Filter (DPF) made of galvalum on exhaust emissions and engine temperature in a Mitsubishi L300 vehicle. The DPF was designed using galvalum material with a square honeycomb configuration and glasswool variations of 50, 100, and 150 grams. The test was conducted experimentally by comparing conditions without DPF and after DPF installation, including testing exhaust emissions, engine oil temperature, radiator water temperature, and exhaust manifold temperature. The installation of a diesel particulate filter (DPF) can reduce exhaust emissions by up to 37.1% at DPF 150 variations. DPF installation also relatively increases the temperature of radiator water, engine oil, and exhaust manifold in diesel engines. The largest temperature increase in exhaust manifold temperature is up to 8.02% compared to without using DPF at idle conditions. This temperature increase is caused by the honeycomb and glasswool structures that can create obstacles to the flow of exhaust gases. When the engine speed reaches 2000 rpm, there is an increase in exhaust manifold temperature of up to 15.09% compared to idle speed. This increase is due to faster engine speed so that combustion heat also increases.